Ground-based APS (aerodynamic particle sizer) data taken at the coast of Andøya, Norway during March 2021 - Robert Oscar David; Tim Carlsen; Astrid Bragstad Gjelsvik; Jörg Wieder; Zamin A Kanji; Trude Storelvmo (PANGAEA, 2025)
During a 2-week measurement campaign from 15-31 March 2021 (ISLAS2021), we collected a comprehensive dataset characterizing the atmospheric water vapour and precipitation stable isotope and aerosol composition at a coastal station in the European sub-Arctic. Located at the northeastern coast of the Nordic Seas, stable water isotope measurements with cavity ring-down spectrometers (CRDS) were collected at Andenes, Norway close to sea level and at the nearby ALOMAR mountain top observatory at 370 m a.s.l. Paired water vapour isotope and precipitation measurements at sub-event time resolution were collected at both station locations. These were supplemented with water vapour isotope measurements at the cities of Tromsø, Norway and Bergen, Norway. Surface precipitation samples were collected on a per-event basis along a transect towards the south to assess spatial representativeness. Measurements of ice nucleating particle concentrations were taken at sea level during precipitation events, supplemented by continuous size-resolved aerosol measurements. These detailed measurements were complemented by additional instrumentation to characterize the atmospheric conditions, including ground-based vertical-pointing rain radars, disdrometer, frequent radiosonde ascents and a ceilometer. All stable water isotope measurements have been calibrated onto the VSMOW-SLAP scale. During the campaign, weather conditions were alternating rapidly between warm mid-latitude air masses and marine cold-air outbreak conditions. The data from the ISLAS2021 measurement campaign therefore provide insight into a variety of mixed-phase precipitation processes, atmospheric long-range transport, and the dynamics of high-latitude weather system with the combined perspective of stable water isotopes and aerosol measurements. This dataset contains measurements of aerosol number size distributions and total concentrations in air from the site Coast near Andenes, Norway, during the ISLAS 2021 field campaign. The primary purpose for the collection of this dataset was to enable paired measurements of aerosols and ice-nucleating particle concentrations at sub-event time resolution. These aerosol measurements were obtained with an aerodynamic particle sizer (APS) installed near the shoreline at the base of the north-facing slope of Andhauet mountain. The observational period lasted about 16 days, from 2021-03-15T09:05:15 to 2021-03-31T07:23:12 UTC, at a 60 second time resolution.
In: Sodemann, Harald; Seidl, Andrew Walter; Thurnherr, Iris; Dekhtyareva, Alena; David, Robert Oscar; Carlsen, Tim; Chandler, David M; Schäfer, Britta; Gjelsvik, Astrid Bragstad; Touzeau, Alexandra; Zannoni, Daniele; Baumgartner, Gerd; Storelvmo, Trude; Wieder, Jörg; Kanji, Zamin A; Flügge, Martin (2025): ISLAS2021: Calibrated stable water isotope measurements and aerosol measurements at the coast of northern Norway during March 2021 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984616